Electroactive biofilms on surface functionalized anodes: The anode respiring behavior of a novel electroactive bacterium, Desulfuromonas acetexigens. (15th October 2020) - Katuri, Krishna P.; Kamireddy, Sirisha; Kavanagh, Paul; Muhammad, Ali; Conghaile, Peter Ó; Kumar, Amit; Saikaly, Pascal E.; Leech, Dónal
Highlights: Hydrophilic anode surfaces promote rapid start-up of current generation. Early stage biofilms on hydrophilic surfaces are dominated by a Desulfuromonas sp . The Desulfuromonas sp. is identified to be D. acetexigens: a novel electroactive bacterium. D. acetexigens has the ability to maximize H2 recovery in a microbial electrochemical system. Abstract: Surface chemistry is known to influence the formation, composition, and electroactivity of electron-conducting biofilms. However, understanding of the evolution of microbial composition during biofilm development and its impact on the electrochemical response is limited. Here we present voltammetric, microscopic and microbial community analysis of biofilms formed under fixed applied potential for modified graphite electrodes during early (90 h) and mature (340 h) growth phases. Electrodes modified to introduce hydrophilic groups (-NH2, -COOH and -OH) enhance early-stage biofilm formation compared to unmodified or electrodes modified with hydrophobic groups (-C2 H5 ). In addition, early-stage films formed on hydrophilic electrodes are dominated by the gram-negative sulfur-reducing bacterium Desulfuromonas acetexigens while Geobacter sp. dominates on -C2 H5 and unmodified electrodes. As biofilms mature, current generation becomes similar, and D. acetexigens dominates in all biofilms irrespective of surface chemistry. Electrochemistry of pure culture D. acetexigens biofilms reveal that this microbe is capable of forming electroactive biofilms producing considerable current density of > 9 A/m 2 in a short period of potential-induced growth (~19 h following inoculation) using acetate as an electron donor. The inability of D. acetexigens biofilms to use H2 as a sole source electron donor for current generation shows promise for maximizing H2 recovery in single-chambered microbial electrolysis cell systems treating wastewaters. Graphical abstract: Image, graphical abstract